Long-term Formation of Aggressive Bony Lesions in Dogs with Mid-Diaphyseal Fractures Stabilized with Metallic Plates: Incidence in a Tertiary Referral Hospital Population - Gilley, Robert S.; Hiebert, Elizabeth; Clapp, Kemba; Bartl-Wilson, Lara; Nappier, Michael; Werre, Stephen; Barnes, Katherine (Frontiers in Veterinary Science, 2017)
The incidence of complications secondary to fracture stabilization, particularly osteolytic lesions and bony tumor formation, has long been difficult to evaluate. The objective of this study was to describe the long-term incidence of aggressive bony changes developing in dogs with long bone diaphyseal fractures stabilized by metallic bone plates compared to a breed, sex, and age-matched control group. The medical records of a tertiary referral center were retrospectively reviewed for dogs that matched each respective criterion. Signalment, history, cause of death (if applicable), and aggressive bony changes at previous fracture sites was recorded. Ninety dogs met the criteria for inclusion in the fracture group and were matched with appropriate control dogs. Four of the dogs in the fracture group developed aggressive bony changes at the site of previous fracture repairs most consistent with osseous neoplasia. One lesion was confirmed with cytology as neoplastic. The population of dogs was mixed with regard to breed and body weight, but all dogs with aggressive bony lesions were male. Incidence of aggressive bony lesion formation in the fracture group was four (4.4%) and was zero (0%) in the control group; three (75%) of the affected dogs in the fracture group included cerclage as a component of their primary fracture stabilizations. Incidence of aggressive bony lesions in the fracture group compared to the control group was determined to be statistically significant (p=0.0455), as was the incidence of cerclage among dogs affected by aggressive bony lesions compared to the rest of the fracture group (p=0.0499). Development of aggressive bony lesions is an uncommon complication of fracture fixation. Additional research is needed to further identify and elucidate the long-term effects of metallic implants in dogs.